Identifying modifiable features of home bowel cancer screening kits to facilitate use: consumer perspectives - Belinda C Goodwin; Bianca Viljoen; Larry Myers; Michael J Ireland; Jeff Dunn; Suzanne K Chambers; Nicholas Ralph |; Joanne F Aitken (Sax Institute, 2022)
Objectives: Despite the widely publicised health benefits of participation in bowel cancer screening, only 43.5% of recipients participate in the Australian National Bowel Cancer Screening Program (NBCSP). Through consultation with kit recipients, this study aimed to identify features of home bowel screening kits that could be modified to increase their use. Method: Participants (n = 25) were presented with nine different bowel cancer screening kits and asked to identify features of each kit that might prevent or promote their use. Responses were coded using content analysis, and a narrative synthesis is presented summarising preferences relating to each element of the kit. Results: Six modifiable elements were identified: collection tool, collection sheet, specimen container, instruction, packaging and processes. Participant preferences were for collection devices that limited the users' proximity to faecal matter, smaller packaging, simpler processes and step-by-step pictorial instructions. Responses regarding aesthetics, the amount of information included and receiving immediate results were mixed. Conclusions: Findings provide several consumer-driven recommendations, which are to be tested in future research aimed at improving the acceptability and usability of kits distributed in population bowel cancer screening programs.